Environmental exposure to metallic soil elements and risk of cancer in the UK population, using a unique linkage between THIN and BGS databases - Musah, Anwar (2017)
Background: There have been many epidemiological studies into the influence of exposure to the most toxic elements on the risk of cancer in the workplace, mainly due to the exposure of certain occupational groups, or perhaps in populations near industrial sources. Toxic elements include arsenic, copper, nickel, and uranium; and many more of these elements have been shown to increase the risk of several different types of cancers in these highly-exposed groups. Many of these elements naturally exist in the soil, and the health impact of these levels of environmental exposures on the general population has received little attention to date possibly due to the belief that soil concentrations of these elements are too low to cause harm to the general population. Therefore, the long-term effect of such chronic exposure to metals in the soil remains unclear.